Consumer's Surplus and Cardinal Utility - Bishop, Robert L. (Quarterly Journal of Economics, 1943)
Three definitions of consumer's surplus, 422. — The assumption of universal independence, 422. — The "marginal-utility demand curve, " 423. — Open-topped marginal utility curves, 426. — Interpersonal and intertemporal comparisons of utility, 426. — Marshall's first version: extra expenditure, 427. — Its diagrammatic analysis, 429. — Nicholson's criticism of Marshall, 432. — Marshall's second version: the demand curve, 433. — Cannan's criticism, 435. — A necessary condition of independence, 437. — Relaxing the independence assumption: (1) One utility independent of all others, 438. — Alternative tests of independence, complementarity, competitiveness, 442. — (2) Independence between groups, 443. — (3) The case of "least independence, " 444. — Summary of basic tests, 447. — Conclusions, 448.